The altruistic lobbyists - Van Rooy, A (1994)
The role of non-governmental organizations (NGOs) has sparked increased interest in recent years as they have grown in prominence and international activity. The thesis looks at British and Canadian NGOs concerned with overseas development assistance, and asks what influence they have wielded in the formulation of their own governments' development policies. Based on recent policy community writing, a "conceptual map" is devised which suggests that six elements are important for any analysis of influence: context, content, motivations, resources, tactics, and channels. Chapters two to five use these elements to look at the broad "policy communities" in which official development policy is formulated, and to examine the increasing roles and activities of NGOs as lobbyists. Chapters six and seven take a closer look at two specific "policy networks" within those communities: the relationships created around the World Food Conference in 1974 are compared with those existing at the time of the 1992 United Nations Conference on Environment and Development (the Earth Summit). The thesis concludes that NGOs have had an increasing but limited influence on government policy, given (1) an increase in the activity and influence of NGOs, (2) the greater relevance of certain "elements of influence" over others, and (3) the comparatively stronger influence of Canadian NGOs in relation to their British counterparts. The thesis' contribution to knowledge is based on its use of extensive and original primary sources and interviews in both countries, its application of a policy community approach to a new field in international relations, and its systematic attempt to answer evolving questions about this growing, international, and non-governmental force.